Cross Ownership and Licensing Incentive - Ayu Sasni Munte (PT FORMOSA CENDEKIA GLOBAL, 2023)
In a homogeneous good Cournot duopoly, a firm owns a cost-reducing technology and shares his ownership to its rival. We show that optimal output of firm 1 is lower under licensing than under no licensing but optimal output of firm 2 is higher under licencing than under no licensing. Superior firm will license its superior technology to firm 2 depends on how effective the technology is.